(untitled) (Journal of the College of Basic Education, 2022)
Social networking scale with autistic children. Identify the social communication between males and females. The research sample consisted of 30 children from the Institute of Imam Hussein (AS) was chosen to unite in intentional. To achieve the objectives of the research, the researcher developed a barometer for social networking component (50) items have been extracted virtual honesty through the show to the group of arbitrators specialists in education, psychology and special education also analyzed paragraphs statistically extracted strength discriminatory characteristics Alsekoumtrah scale social networking and is honesty through the (para link college degree and a link to the field domain to which it belongs and appreciation stability Alvakronbach way and re-testing) the application has become the ultimate measure of his image consists of (45) items was applied to a sample consisting of 30 boys and girls. The research has come to the results as follows: 1-that children with autism do not have a social communication on the social networking scale. 2-This is referred to by some researchers and specialists to show that there are differences between males and females, with females found that autistic children show higher than average abilities shown by males infected children with autism, whether they are children or adults. As a complement to the requirements of search researcher has made a number of recommendations and proposals from them. Recommendation: 1-the importance of supporting and activating the training programs that scientific studies have proven its effectiveness in the training of children with autism. 2-A’s teachers and special education teachers used measure of social networking skills as a diagnostic tool for the detection of children who suffer from the weakness of the social networking skills. Suggestions: 1-Conduct a case study for all autistic children because every child is different from the case of jealousy 2-conduct a study on the impact of nutrition, medicine and oxygen for the treatment of autism cases